2010
DOI: 10.1080/19415250903126043
|View full text |Cite
|
Sign up to set email alerts
|

School culture and postgraduate professional development: delineating the ‘Enabling School’

Abstract: The culture of the 'enabling school' is investigated within the context of the government's policy of continuing professional development and postgraduate professional development for teachers in England. This context is problematised by considering teachers' conceptualisations of their professional autonomy, status and personal expertise. A small purposive sample of schools and colleges provided the case studies for this research. Semi-structured interviews were conducted with teachers and continuing professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…There is a tension here. The pressure of performativity agendas and performance management linked to attainment is at odds with the concept of coaching, and there is evidence that most of the difficulties experienced in coaching in schools (and the confusion between this and mentoring) arise from making the coaching process part of the school improvement system through performance management of teachers (Arthur 2009). …”
Section: Coaching In Schoolsmentioning
confidence: 99%
“…There is a tension here. The pressure of performativity agendas and performance management linked to attainment is at odds with the concept of coaching, and there is evidence that most of the difficulties experienced in coaching in schools (and the confusion between this and mentoring) arise from making the coaching process part of the school improvement system through performance management of teachers (Arthur 2009). …”
Section: Coaching In Schoolsmentioning
confidence: 99%
“…However, while CPD may be linked to an enhanced sense of professionalism, this is not necessarily sufficient to compete with the negative impact on professionalism generated by the everincreasing workload and pressure to meet targets and raise standards. As Arthur et al (2009) argue, there is a tension between the desire to improve the status of teachers and a performance management approach with increased pressure to raise standards which are likely to serve to reduce teacher status.…”
Section: Raising the Status Of The Teaching Professionmentioning
confidence: 99%
“…Research literature on teachers' collaboration and reflective practices has shown that professional exchange about teaching can boost professional development where as its absence can have a negative effect (Arthur et al 2010;Beresford and West 1998;Brady 2009;Bryk et al 1999;Butler et al 2004;Conner 2004;Day, Hadfield and Kellow 2002;Huntley 2005;Hopkins and Stern 1996;Hopkins, Naysmith and Palma 1998;Jolliffe and Hutchinson 2007;Lieberman 2009;McCotter 2001;Minnet 2003;Priestley and Sime 2005;Sarsar 2008;Saunders 2005;Talbert and McLaughlin 2002;Wilson 2008). With this study, I explored further why reflection on practice which remains private can have a limiting effect on professional development.…”
mentioning
confidence: 97%